الصراع بين الثقافة والعصرنة في الخطاب البصري الكرافيكي - غزوان، معتز عناد (المجمع العلمي العراقي, 2016)
The graphic design is considered a visual discourse, affecting a receiver (the individual) or a group of receivers (the society). It is a sort of visual mobile message, moving in its constituents to the receiver's imagination in such a way as to reveal the responses to the design (the visual discourse), being the discourse tool of the designer directed to the receiver.
يعد التصميم الكرافيكي خطابا بصريا مؤثرا في المتلقي (كفرد) أو مجموعة المتلقين (كمجتمع)، وهو بمثابة الرسالة البصرية المتحركة التي تنتقل بمكوناتها إلى مخيلة المتلقي مما يكشف عن ردود الأفعال اتجاه التصميم (الخطاب البصري) بوصفه الأداة الخطابية للمصمم نحو المتلقي.
Keywords: التصميم الجرافيكي -- العولمة -- تكنولوجيا المعلومات -- الفنون البصرية